2021
DOI: 10.1021/acs.jchemed.1c00200
|View full text |Cite
|
Sign up to set email alerts
|

Case Study Teaching for Active Learning on Analytical Quality Assurance Concepts in Relation to Food Safety Exposure Assessment

Abstract: For food research, control, and production, valid and trustworthy analytical data are important. Our practical chemical food safety course for engineers therefore uses real-life studies for the ease of understanding the concept and the needed requirements for high analytical quality in relation to enabling correct evaluation of chemical food safety. Concepts of chromatography and mass spectrometry were applied and left open for inquiry-based learning and students' search for information for their actual case s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 18 publications
(32 reference statements)
0
4
0
Order By: Relevance
“…Further research will also explore ecological validity to gain insights from practitioners’ perspectives to enhance practical relevance. Additionally, future research should explore active approaches and digitally enabled teaching and learning approaches to educate future food safety professionals [ 87 , 88 ]. This is important as such strategies could be beneficial in producing well-rounded practitioners who would not only be proactive, but also be able to address challenges with food safety culture assessments, challenge assumptions, and establish the field as has been done in other culture domains.…”
Section: Discussionmentioning
confidence: 99%
“…Further research will also explore ecological validity to gain insights from practitioners’ perspectives to enhance practical relevance. Additionally, future research should explore active approaches and digitally enabled teaching and learning approaches to educate future food safety professionals [ 87 , 88 ]. This is important as such strategies could be beneficial in producing well-rounded practitioners who would not only be proactive, but also be able to address challenges with food safety culture assessments, challenge assumptions, and establish the field as has been done in other culture domains.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of ICP-MS in real-world analytical chemistry applications has led to a number of proposed student lab exercises using ICP-MS over the past decade. Such protocols are of great pedagogical value and introduce students to foundational concepts of ICP-MS and the practical application of the technique. However, important analytical chemistry concepts such as the impact of matrix effects on the accuracy of ICP-MS analysis and parameter optimization via the usage of a standard reference material (SRM), which should closely mimic the composition of the sample, have not been extensively explored in previously published student-led ICP-MS experiments. Here we introduce a hands-on lab exercise for an upper-division undergraduate analytical chemistry course that mimics industry- and government-level ICP-MS protocols.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the Journal of Chemical Education literature indicated there are no publications reporting the analysis of tocopherols by HPLC or the use of PFP columns. There are just two publications that detail the application of HPLC with FL detection for quantitative analysis. , There are four publications that deal with QuEChERS: two focused on the analysis of pesticides/insecticide residues in food using gas chromatography; , the other two papers, while including QuEChERS in the experimental details, were reporting on the value of standard operating procedures and the importance of quality assurance measures …”
Section: Introduction and Rationalementioning
confidence: 99%
“…5,6 There are four publications that deal with QuEChERS: two focused on the analysis of pesticides/insecticide residues in food using gas chromatography; 7,8 the other two papers, while including QuEChERS in the experimental details, were reporting on the value of standard operating procedures 9 and the importance of quality assurance measures. 10 In summary, the pedagogical aims of this experiment are the following: (a) to support the theory presented in lectures and provide students with an opportunity to apply their theoretical knowledge and understanding of separation mechanisms to a real exampleespecially as analysis of tocopherols has evolved over time from silica stationary phases (normal phase) to C18 phases and more recently PFP phases; (b) to introduce students to the sensitivity and selectivity of FL detection when compared to UV−vis; (c) to provide students with a relatively complex and authentic analysis that includes sample preparation and cleanup and quantitative HPLC analysis using the method of internal standards; (d) to provide students with an opportunity to consolidate their learning of key theoretical concepts and demonstrate their understanding through completing a written report.…”
Section: ■ Introduction and Rationalementioning
confidence: 99%